Sex hormone status may modulate rate of expansion of proximal femur diameter in older women alongside other skeletal regulators. - Kaptoge, S; Dalzell, N; Folkerd, E; Doody, D; Khaw, K; Beck, T; Loveridge, N; Mawer, E; Berry, J; Shearer, M; Dowsett, M; Reeve, J (2007)
CONTEXT: Little is known of associations between hip geometry and skeletal regulators. This is important because geometry is a determinant of both hip function and resistance to fracture. OBJECTIVE: We aimed to determine the effects of sex hormone status and other candidate regulators on hip geometry and strength. SUBJECTS AND METHODS: A random sample of 351 women aged 67-79 had two to four hip dual-energy x-ray absorptiometry scans performed over 8 yr of follow-up. Hip structural analysis software was used to measure subperiosteal diameter (PD) and the distance from the center of mass to the lateral cortical margin (d-lat) on three 5-mm-thick cross-sectional regions: narrow neck, intertrochanter, and shaft. Section modulus (Z), bone mineral density (grams per centimeter squared), and an index of bone mineral content (cross-sectional area) were calculated as estimators of bone strength. Serum analytes measured at baseline included SHBG, estradiol, PTH, creatinine, albumin, vitamin D metabolites, and glutamate- and gamma-carboxyglutamate-osteocalcin (OC). A linear mixed model was used to model associations with predictor variables, including testing whether the predictors significantly modified the effect of aging. RESULTS: Aging was associated with increasing PD and d-lat, and higher baseline SHBG significantly modified this effect, in the case of PD, increasing the rates of change at the narrow neck region by 19% for SHBG level 2 sd higher than population mean (P = 0.026). Higher baseline creatinine was independently associated with faster increases in PD and d-lat with aging (P < 0.041). Z declined faster with aging if baseline PTH was higher, and higher albumin had a contrary effect. Z was positively associated with free estradiol and inversely associated with SHBG and glutamate-OC. CONCLUSION: These results show large effects of SHBG on the regulation of proximal femur expansion and bending resistance, probably acting as a surrogate for low bioavailable estrogen. Potentially important effects for fracture resistance in old age were also revealed for PTH, markers related to renal function and the nutritional markers albumin and undercarboxylated OC.